Efficacy Test of Bio-pesticides against Tobacco Whitefly Bemisia tabaci (Gennadius, 1889) on Tomato Plants in Nepal - Sharma, M.; Budha, P.B.; Pradhan, S.B. (Journal of Institute of Science and Technology, 2015)
The efficacy test of bio-pesticides (Lastraw, RacerTM PacerTM, MealikilTM, Nimbecidine, Servo, Biocide Manic, Bio Power, Nico Neem, Uchit, Mighty-Cure, and Bio Magic) was experimented in tomato plants to control Tobacco whitefly Bemisia tabaci population. The results showed that biopesticides viz. Bio Magic (92.67%), Racer (91.90%), Pacer (91.50%), Mealikil (90.84%) were highly effective following Bio Power (87.53%) and Biocide Manic (85.8%) in reducing the population of whitefly over control after third spray. All biopesticides containing insect pathogen Beauveria bassiana, Verticillium lecanii and Metarhizium anisopliae were found effective in reducing the pest population. But the organic products and mineral oil were comparatively less effective. Journal of Institute of Science and Technology, 2015, 20(2): 11-17